2010
DOI: 10.1002/pen.21744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compatibilizer on the co‐continuity and nanoclay dispersion level of tpe nanocomposites based on PP/EPDM

Abstract: The effects of different polypropylene (PP)‐g‐maleic anhydride polymers, used as compatibilizers, on the degree of exfoliation and co‐continuity of PP/ethylene‐propylene‐diene terpolymer (EPDM) thermoplastic elastomer (TPE)/clay nanocomposites were investigated. X‐ray diffraction and transmission electron microscopic micrographs showed that nanocomposites ranged from intercalated structure to a coexistence of intercalated tactoids and exfoliated layers. The observed significant increase in crystallization temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The materials selected for the present study are described below. They were chosen based on our previous work [18]. General purpose PP homopolymer resin, “Profax” 6523 (Basell Polyolefins), with melt flow index of 4 (g/10 min), was used as the thermoplastic phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The materials selected for the present study are described below. They were chosen based on our previous work [18]. General purpose PP homopolymer resin, “Profax” 6523 (Basell Polyolefins), with melt flow index of 4 (g/10 min), was used as the thermoplastic phase.…”
Section: Methodsmentioning
confidence: 99%
“…Two grades of maleic anhydride‐grafted‐PP (PP‐ g ‐MA), Orevac CA 100 and Orevac 18750 (Arkema), were chosen, in view of our previous study [18], as compatibilizers to prepare PP nanocomposites with different clay dispersion levels. Irganox B 225 (Ciba) primary phenolic type antioxidant was used in order to prevent oxidative degradation of thermoplastic phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained data showed that the nanocomposites ranged from intercalated tactoids and exfoliated layers. Other investigations suggest that higher levels of EPDM could be incorporated into the semi-exfoliated system before losing matrix continuity (87).…”
Section: Thermoplastic-elastomer Polymer Blend Nanocompositesmentioning
confidence: 99%